- 4

- 0

## Main Question or Discussion Point

In the prove of the Schrodinger equation preserves the normalization I don't understand the step

from

∂ψ/∂t=ih/2m ∂2ψ/∂x2- i/h Vψ

to

∂ψ*/∂t=-ih/2m ∂2ψ/∂x2+ i/h Vψ* (h represents h bar)

the book says "taking complex conjugate equation" but I don't see how.

Thanks in advance.

from

∂ψ/∂t=ih/2m ∂2ψ/∂x2- i/h Vψ

to

∂ψ*/∂t=-ih/2m ∂2ψ/∂x2+ i/h Vψ* (h represents h bar)

the book says "taking complex conjugate equation" but I don't see how.

Thanks in advance.